Evaluation of Plant Protection Practices of Garlic Growers in Gaziantep Province - Aydın Atakan; Oktay Erdoğan; Hülya Özgönen Özkaya (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to determine the plant protection practices of the garlic growers in Gaziantep province. For this purpose, a survey consisting of 20 questions and based on simple random sampling method was conducted with 81 growers in each of the districts of Araban, Oguzeli, Yavuzeli, Central, Nurdagı, Nizip and Karkamış districts in 2018. The data evaluated and expressed as percent ratio. According to the findings from the surveys, garlic growers stated that they preferred pesticide dealers suggestions for the selection and determination of doses of pesticides used in pests and diseases, they also stated that the price and expiration date were not an important factor in the selection of pesticides. In addition, it is found that growers avoid using the same pesticide continuously against same diseases and pests, they do not make any changes in there commended pesticide doses, pesticides leave residues on the products, they paid attention the time between the last application and harvest. It has been reported that the use of protective clothing and mask during the application by the growers is relative, they do not use pesticides as a mixture, they apply different processes to empty pesticide boxes. It was determined that garlic growers prefered chemical control and did not have knowledge about the concept of biopesticides.